2023
DOI: 10.47836/pjtas.46.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review of Cratoxylum Genus: Ethnomedical Uses, Phytochemistry, and Pharmacological Properties

Abstract: In the past, the Cratoxylum genus has often been utilized as traditional medicines, culinary ingredients, health supplements, as well as manufacturing materials. This flowering plant genus belongs to the family Hypericaceae and is classified into six species: Cratoxylum arborescens, Cratoxylum cochinchinense, Cratoxylum formosum, Cratoxylum glaucum, Cratoxylum maingayi, and Cratoxylum sumatranum. The Cratoxylum genus is native to Asia as a traditional medicinal plant. It is currently being translated into conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…The process entails sequentially testing fractionated material for its activity in a bioassay and assessing its purity through analytical techniques (Weller 2012;Perera et al 2019;Phukhatmuen et al 2020;Afsar et al 2022). Therefore, the chemotaxonomic approach identifies the polyphenol content with the antimalarial activity of the genus Cratoxylum (Lian Ee et al 2013;Juanda et al 2019;Yin Bok et al 2023). Consequently, developing new antimalarial drugs, particularly from Cratoxylum glaucum leaves, is crucial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process entails sequentially testing fractionated material for its activity in a bioassay and assessing its purity through analytical techniques (Weller 2012;Perera et al 2019;Phukhatmuen et al 2020;Afsar et al 2022). Therefore, the chemotaxonomic approach identifies the polyphenol content with the antimalarial activity of the genus Cratoxylum (Lian Ee et al 2013;Juanda et al 2019;Yin Bok et al 2023). Consequently, developing new antimalarial drugs, particularly from Cratoxylum glaucum leaves, is crucial.…”
Section: Resultsmentioning
confidence: 99%
“…According to reports, the Cratoxylum genus could be investigated as a viable plant candidate for discovering novel antimalarial compounds. Major categories of polyphenolic compounds with antimalarial action have been identified in Cratoxylum, including xanthone, flavonoids, quinones, anthraquinones, and phenols (Lian Ee et al 2013;Juanda et al 2019;Yin Bok et al 2023). Extracts of bark from n-hexane of C. maingayi and ethyl acetate of C. cochinchinense have been successfully identified for their bioactive antimalarial compounds such as vismione B (IC 50 0.66 µg/mL), formoxanthone C (IC 50 1.19 µg/mL), macluraxanthone (IC 50 1.35 µg/mL), gerontoxanthone I (IC 50 1.68 µg/mL), and fuscaxanthone E (IC 50 3.02 µg/mL) (Laphookhieo et al 2009).…”
Section: )mentioning
confidence: 99%
“…The process entails sequentially testing fractionated material for its activity in a bioassay and assessing its purity through analytical techniques (Weller 2012;Perera et al 2019;Phukhatmuen et al 2020;Afsar et al 2022). Therefore, the chemotaxonomic approach identifies the polyphenol content with the antimalarial activity of the genus Cratoxylum (Lian Ee et al 2013;Juanda et al 2019;Yin Bok et al 2023). Consequently, developing new antimalarial drugs, particularly from Cratoxylum glaucum leaves, is crucial.…”
Section: Resultsmentioning
confidence: 99%
“…According to reports, the Cratoxylum genus could be investigated as a viable plant candidate for discovering novel antimalarial compounds. Major categories of polyphenolic compounds with antimalarial action have been identified in Cratoxylum, including xanthone, flavonoids, quinones, anthraquinones, and phenols (Lian Ee et al 2013;Juanda et al 2019;Yin Bok et al 2023). Extracts of bark from n-hexane of C. maingayi and ethyl acetate of C. cochinchinense have been successfully identified for their bioactive antimalarial compounds such as vismione B (IC 50 0.66 µg/mL), formoxanthone C (IC 50 1.19 µg/mL), macluraxanthone (IC 50 1.35 µg/mL), gerontoxanthone I (IC 50 1.68 µg/mL), and fuscaxanthone E (IC 50 3.02 µg/mL) (Laphookhieo et al 2009).…”
Section: )mentioning
confidence: 99%
“…The two substances showed high activity against T47D cells with an IC 50 of 1.10 and 1.60 μg/mL, respectively [ 7 ]. Bok et al [ 8 ] reviewed research into the Cratoxylum species and reported on their wide spectrum of phytoconstituents including xanthones, triterpenoids, flavonoids, and phenolic compounds. These compounds explain the plants’ significant pharmacological effects, such as their antibacterial, antifungal, antioxidant, antimalarial, anti-gastric ulcer, anti-HIV-1 reverse transcriptase, antidiabetic, and anti-cancer activities.…”
Section: Introductionmentioning
confidence: 99%